Comparison of the intraoperative efficacy of the powered rasp and conventional burr in arthroscopic resection of anterior ankle osteophytes. Issue 8 (December 2021) - Park, Young Hwan; Kim, Woon; Choi, Jung Woo; Choi, Gi Won; Kim, Hak Jun
Highlights: Rotatory motion of the conventional burr can potentially damage the surrounding soft tissue during arthroscopic surgery. Powered rasp is a new arthroscopic device that uses a reciprocating motion of rasp surface. Powered rasp did not show superior efficacy than conventional burr in arthroscopic osteophyte resection in the ankle joint. Abstract: Background: The efficacy of the powered rasp, a new reciprocating motion device for arthroscopic resection of osteophytes, has not been verified. The aim of this study was to compare the intraoperative efficacy of the powered rasp in arthroscopic resection of anterior ankle osteophytes to that of the conventional burr. Methods: A total of 49 consecutive patients who underwent arthroscopic resection of anterior ankle osteophytes (26 patients with the conventional burr and 23 patients with the powered rasp) were retrospectively reviewed. The preoperative volume of each osteophyte was measured using computerized tomography scan and three-dimensional software. The resection time was measured by review of the individual arthroscopy video, and the estimated resection rate was calculated as the volume of osteophytes/resection time. Results: The preoperative volume of osteophytes was not different between the two groups (847.8 ± 685.3 mm 3 in the conventional burr and 913.3 ± 605.8 mm 3 in the powered rasp, p = 0.726). The resection time was 442.4 ± 216.6 s (seconds) in the conventional burr and 386.4 ± 186.3 s in the powered rasp, and the estimated resection rate was 1.8 ± 1.0 mm 3 /s with the conventional burr and 2.4 ± 1.3 mm 3 /s with the powered rasp. These measurements were not significantly different between the two groups ( p = 0.340 and 0.083, respectively). Conclusion: The intraoperative efficacy of the powered rasp did not show superiority to that of the conventional burr in arthroscopic resection of anterior ankle osteophytes. Level of evidence: Level III, retrospective comparative study.